1999
DOI: 10.1029/1999wr900118
|View full text |Cite
|
Sign up to set email alerts
|

Derivation of equivalent pipe network analogues for three‐dimensional discrete fracture networks by the boundary element method

Abstract: Abstract. Discrete fracture network (DFN) models generally require solution of flow and transport equations in three-dimensional networks of either disc, polygonal, or pipe elements. Pipe network elements have significant advantages in computation for both flow and transport. However, there is a need to develop an efficient procedure for derivation of the properties of these pipes to ensure that they are hydraulically equivalent to the DFN network of polygonal elements. In this study a boundary element procedu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
81
0

Year Published

2002
2002
2020
2020

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 186 publications
(81 citation statements)
references
References 6 publications
0
81
0
Order By: Relevance
“…Many factors can affect the magnitude of permeability of fractured rock masses, including fracture length [28][29][30][31], aperture [32][33][34], surface roughness [35,36], dead-end [37], number of intersections [38,39], hydraulic gradient [40], boundary stress [41,42], anisotropy [43][44][45][46], scale [47][48][49][50], stiffness [51], coupled thermo-hydro-mechanical-chemical (HTMC) processes [52][53][54][55], and precipitation-dissolution and biogeochemistry [56]. The discrete fracture network (DFN) model, which can consider most of the above parameters, has been increasingly utilized to simulate fluid flow in the complex 2 Geofluids fractured rock masses [57][58][59][60], although it cannot model the aperture heterogeneity of each fracture [61][62][63]. In the numerical simulations and/or analytical analysis, the linear governing equation such as the cubic law is solved to simulate fluid flow in fractures by applying constant hydraulic gradients ( ) on the two opposing boundaries, such as = 1 [57,[64][65][66][67][68]], = 0.1 …”
Section: Introductionmentioning
confidence: 99%
“…Many factors can affect the magnitude of permeability of fractured rock masses, including fracture length [28][29][30][31], aperture [32][33][34], surface roughness [35,36], dead-end [37], number of intersections [38,39], hydraulic gradient [40], boundary stress [41,42], anisotropy [43][44][45][46], scale [47][48][49][50], stiffness [51], coupled thermo-hydro-mechanical-chemical (HTMC) processes [52][53][54][55], and precipitation-dissolution and biogeochemistry [56]. The discrete fracture network (DFN) model, which can consider most of the above parameters, has been increasingly utilized to simulate fluid flow in the complex 2 Geofluids fractured rock masses [57][58][59][60], although it cannot model the aperture heterogeneity of each fracture [61][62][63]. In the numerical simulations and/or analytical analysis, the linear governing equation such as the cubic law is solved to simulate fluid flow in fractures by applying constant hydraulic gradients ( ) on the two opposing boundaries, such as = 1 [57,[64][65][66][67][68]], = 0.1 …”
Section: Introductionmentioning
confidence: 99%
“…Bour and Davy (1998) studied the connectivity of 3-D fault networks, and found that faults larger than a critical length scale may form a well-connected fracture network, while smaller faults may be not connected on average. Dershowitz and Fidelibus (1999) established DFN models using the pipe network elements, and developed a boundary element procedure for derivation of pipe properties. Their results agreed well with those of polygonal-element models.…”
Section: Three-dimensional Fracture Networkmentioning
confidence: 99%
“…The 3D structure resulting of the superimposition of the connected portions of planes is thus treated as a 3D network of 1D pipes as in Cacas et al (1990). Equivalence of this channel flow approach with others solving true 2D flow in planes has been discussed (Dershowitz and Fidelibus, 1999).…”
Section: Hydraulic Conductivitiesmentioning
confidence: 99%